La poesia de Pere Gimferrer, entre la literatura i l’autobiografia - Sala-Valldaura, Josep Maria (Caplletra. Revista Internacional de Filologia, 1997)
In this article the general coordinates of the poetry of Pere Gimferrer are defined, from certain philosophical and literary influences —idealism, oriental thought, symbolism, the theories of Octavio Paz— and from autobiographical information present in some of his poems. Also, these and other different factors seen in the poet’s books are studied.